A systematic review and meta-analysis study of salivary and serum interleukin-8 levels in oral lichen planus - Mozaffari, Hamid Reza (Postepy Dermatol Alergol, 2018)
INTRODUCTION: Interleukin-8 (IL-8) is an important mediator of the host response to injury and inflammation that the clinical severity of oral lichen planus (OLP) is associated with elevated serum IL-8 levels. AIM: To evaluate serum and salivary IL-8 levels of the OLP patients compared with the healthy controls and measurement of IL-8 level in which sample is more valuable. MATERIAL AND METHODS: Five databases including PubMed/Medline, Web of Science, Science Direct, Cochrane Library and Scopus were searched for the evaluation of serum and salivary IL-8 levels of the OLP patients compared with the healthy controls in the English abstract. The Newcastle-Ottawa Quality Assessment Scale (NOS) was used for checking the quality of the studies. A random-effect model was used for calculating the mean difference (MD) and 95% confidence intervals (CIs). RESULTS: Nine studies were included in the meta-analysis. The pooled estimate showed a significant difference between two groups that the salivary IL-8 level in the OLP patients was higher than the healthy controls (MD = 766.32 pg/ml, 95% CI: 394.90–1137.75; p < 0.0001) and also the serum IL-8 level in the OLP patients was higher than the healthy controls (MD = 8.38 pg/ml, 95% CI: 3.32–13.44; p = 0.001). CONCLUSIONS: The higher levels of IL-8 in saliva compared with serum suggest that measurement of this marker in saliva may be more useful than serum measurements for determining therapeutic and diagnostic aims.